2000
DOI: 10.1007/s11743-000-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary odorants of laundry soiled with sweat/sebum: Influence of lipase on the odor profile

Abstract: Odorants still attached to laundry soiled with human axillary sweat and sebum after a mild washing procedure [European full-scale, short-cycle wash (20 min wash, 15 min rinse) at 30°C, using color detergent at 3.5 g/L] were extracted and analyzed by aroma extract dilution analysis. Esters (ethyl-2-methylpropanoate and ethylbutanoate), ketones (1-hexen-3-one and 1-octen-3-one) and, in particular, aldehydes [(Z)-4-heptenal, octanal, (E)-2-octenal, methional, (Z)-2-nonenal, (E,Z)-2,6-nonadienal, (E,Z)-2,4-nonadie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 14 publications
2
67
1
Order By: Relevance
“…Although, the main component of this fluid is water (up to 98%), it also contains glicoproteins, lactic acid, sugars, amino acids and electrolytes. This sweat is originated from the extracellular fluid so it reflects the compounds present in the blood plasma [41]. In turn, apocrine glands are only present in the armpit, pubic area and areola.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the main component of this fluid is water (up to 98%), it also contains glicoproteins, lactic acid, sugars, amino acids and electrolytes. This sweat is originated from the extracellular fluid so it reflects the compounds present in the blood plasma [41]. In turn, apocrine glands are only present in the armpit, pubic area and areola.…”
Section: Introductionmentioning
confidence: 99%
“…Pure apocrine secretions are both odorless and sterile when first appearing on the skin's surface [25]. Apocrine secretion is known to contain steroid sulfates, cholesterol, and proteins [26].…”
Section: Apocrine Glandsmentioning
confidence: 99%
“…Pure eccrine secretions have been shown to be white in appearance [25], and typically composed o f 98% water, but it also contains various organic and inorganic components [23]. Eccrine sweat originates in the extracellular fluid and, therefore, reflects the chemistry o f blood plasma [26]. The volatile components o f blood have been identified (Appendix B) and include alcohols, aldehydes, and alkanes [27,28].…”
Section: Eccrine Glandsmentioning
confidence: 99%
“…When a glove was placed over the hand, the air flow slowed at first, but then eventually appeared to escape through the glove at a normal rate. Most studies have focused on apocrine-gland secretions in the axilla 26,34,[59][60][61][62] as they contribute largely to body malodor. It has been suggested that the precursors of odorous compounds are transported to the surface of the skin by carrier proteins where they interact with the microflora in this region to create odor.…”
Section: Production and Transmission Of Human Scentmentioning
confidence: 99%
“…The most common method has been to wipe sweat from an area of the body with gauze or a similar material, then to extract the sweat from the material. 26,34,[59][60][61] Another method has been to extract the sweat directly from a piece of clothing worn by the subject. 54,68 Such methods have tended to recover mostly short-chain fatty acids, in particular, the C 6 -C 11 straight-chain and branched acids, 54,59-61 iso-valeric acid, 54,69 and (E)-3-methyl-2-hexenoic acid 60,61 have been major…”
Section: Production and Transmission Of Human Scentmentioning
confidence: 99%